Producción científica de estudiantes de medicina de la universidad de San Martin de Porres, Perú durante el período 2005-2016 - Ponce-Torres, Christian (2018)
Introduction: Medical schools often include courses related to research in their curriculum, many of which guidel ines the student in the execution of curricular research. However, in Peru, a country with scarce scientific production, these works are not usually published in indexed scientific journals, which drastically limits their visibility and impact. Objective: To characterize the scientific production of undergraduate students of the Human Medicine School of University of San Martin de Porres, during the period 2005-2016. Methods: Bibliometric study. A bibliographic search was carried out in the web portals of the databases SCOPUS, SciELO, LILACS and LIPECS, using terms that identify the FMH-USMP. We selected the articles that had a student of the Human Medicine School of University of San Martin de Porres as author. Subsequently, the characteristics of interest for each article were collected. The statistical analysis was carried out with the statistical software Stata v13. Results: A total of 160 scientific publications with student participation were found. On average, 1.63 % of the students of the Human Medi cine School of University of San Martin de Porres participated in some scientific publication yearly. Among the articles evaluated, 39 (24.4 %) were published in journals indexed to Scopus, 31.3 % and 55.6 % had as their first author and correspondent author a student of the Human Medicine School of University of San Martin de Porres, respectively, while 66.9 % had the participation of students from one of the scientific societies of medical students (SOCEM) of the Human Medicine School of the University of San Martin de Porres. In addition, 65.0 % are original articles, among which 60.6 % were descriptive observational studies.